2022
DOI: 10.1093/ofid/ofac516
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Measures of Adherence to Isoniazid Preventive Therapy Among People With HIV in Uganda

Abstract: Background Isoniazid (INH) preventative therapy is recommended for people with HIV (PWH) in resource-constrained settings. Valid measures are needed to assess adherence. We aimed to examine agreement between measures overall and by level of social desirability. Methods PWH with latent TB were recruited in Mbarara, Uganda. Past 30-day adherence was measured by the number of days with pill bottle openings using a Medication Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A high discrepancy between self or caregiverreported adherence and urine biomarker tests was also reported by a study that assessed adherence in HIVexposed infants enrolled in a TB prevention trial in western Kenya [31]. Several other studies have reported discrepancies between self-giver or caregiver reported versus biomarker-confirmed adherence [17,35]. The growing evidence that self-giver or caregiver reports overestimate adherence suggests the need for more objective measures of adherence to TB preventive therapy [17,35].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A high discrepancy between self or caregiverreported adherence and urine biomarker tests was also reported by a study that assessed adherence in HIVexposed infants enrolled in a TB prevention trial in western Kenya [31]. Several other studies have reported discrepancies between self-giver or caregiver reported versus biomarker-confirmed adherence [17,35]. The growing evidence that self-giver or caregiver reports overestimate adherence suggests the need for more objective measures of adherence to TB preventive therapy [17,35].…”
Section: Discussionmentioning
confidence: 79%
“…Several other studies have reported discrepancies between self-giver or caregiver reported versus biomarker-confirmed adherence [17,35]. The growing evidence that self-giver or caregiver reports overestimate adherence suggests the need for more objective measures of adherence to TB preventive therapy [17,35]. Biomarker confirmation of actual drug exposure provides a more accurate and objective measure of adherence [16,17,20] and could be useful in identifying nonadherent CLHIV in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%